Lembaga Keuangan Mikro dan Pengentasan Kemiskinan: Kasus Lumbung Pitih Nagari di Padang - Sila, Muhammad Adlin (Masyarakat: Jurnal Sosiologi, 2010)
This study explores the advent of microfinance institution that has been an important development in recent years. Through case study on one microfinance institution namely lumbung pitih nagari located in Padang, West Sumatra, Indonesia, this study found that the existence of the micro credit institute has been influenced by several factors such as state regulations. In 1997, the central bank of Indonesia (BI) carried out regulatory reforms in order to reduce the risk of bank failures. This regulation in fact has weakened the role of microfinance institutions in giving financial services to small-medium enterprises (SMEs). However, in the reformation era, many local microfinance institutions emerge as the Ministry of Cooperation and Small-Medium Enterprises has officially given support for the betterment of SMEs through soft loan mechanism. LPN has been one of its kind which is able to run profitably and at the same time to facilitate credit for SMEs in the region.